Designs for phase I trials in ordered groups. (14th September 2016) - Conaway, Mark R.; Wages, Nolan A.
Abstract : We propose a new design for dose finding for cytotoxic agents in two ordered groups of patients. By ordered groups, we mean that prior to the study there is clinical information that would indicate that for a given dose one group would be more susceptible to toxicities than patients in the other group. The designs are evaluated relative to two previously proposed designs for ordered groups over a range of scenarios generated randomly from a family of dose‐toxicity curves. Copyright © 2016 John Wiley & Sons, Ltd.